(untitled) (The Review of Diabetic Studies, 2025)
Background: Accommodative spasm (pseudomyopia or ciliary spasm) is a rare ocular disorder characterized by intermittent blurred distance vision, headaches, and eye strain. Often misdiagnosed as true myopia, its prevalence is increasing with prolonged near work and digital screen use, especially among adolescents and young adults. Aim: This review synthesizes recent evidence on the etiology, diagnosis, management, and treatment of accommodative spasm to provide updated clinical guidance. Methods: A systematic literature search was conducted across PubMed, Scopus, ScienceDirect, EMBASE, Web of Science, and Google Scholar for English-language studies published between January 2020 and March 2025. Eleven peer-reviewed articles met inclusion criteria. Data extraction followed PRISMA guidelines, and methodological quality was appraised using JBI and AMSTAR 2 tools. Findings: Accommodative spasm is predominantly functional in origin, strongly associated with intensive near visual demands. Cycloplegic refraction remains essential for differential diagnosis. Pharmacological management with cycloplegics (atropine, cyclopentolate, tropicamide) is effective in acute control, while optical correction, vision therapy, ergonomic modifications, and stress reduction strategies play a central role in long-term management. Innovative diagnostic methods (e.g., cyclodamia, dynamic autorefractors) and digital vision therapy programs are emerging. Multidisciplinary care, and in rare refractory cases, surgical interventions such as clear lens extraction, may be required. Conclusion: Early recognition and accurate diagnosis are crucial to avoid mismanagement. A multimodal approach combining pharmacologic and non-pharmacologic strategies offers the best outcomes. Personalized care, lifestyle modifications, and patient education are essential to reduce recurrence and preserve visual function in populations increasingly exposed to digital visual demands.